(untitled) (Clinics, 2012)
OBJECTIVES: Tension cost, the ratio of myosin ATPase activity to tension, reflects the economy of tension development in the myocardium. To evaluate the mechanical advantage represented by the tension cost, we studied papillary muscle contractility and the activity of myosin ATPase in the left ventricles in normal and pathophysiological conditions. METHODS: Experimental protocols were performed using rat left ventricles from: (1) streptozotocin-induced diabetic and control Wistar rats; (2) N-nitro-L-arginine methyl ester (L-NAME) hypertensive and untreated Wistar rats; (3) deoxycorticosterone acetate (DOCA) salt-treated, nephrectomized and salt- and DOCA-treated rats; (4) spontaneous hypertensive rats (SHR) and Wistar Kyoto (WKY) rats; (5) rats with myocardial infarction and shamoperated rats. The isometric force, tetanic tension, and the activity of myosin ATPase were measured. RESULTS: The results obtained from infarcted, diabetic, and deoxycorticosterone acetate-salt-treated rats showed reductions in twitch and tetanic tension compared to the control and sham-operated groups. Twitch and tetanic tension increased in the N-nitro-L-arginine methyl ester-treated rats compared with the Wistar rats. Myosin ATPase activity was depressed in the infarcted, diabetic, and deoxycorticosterone acetate salt-treated rats compared with control and sham-operated rats and was increased in N-nitro-L-arginine methyl ester-treated rats. These parameters did not differ between SHR and WKY rats. In the studied conditions (e.g., post-myocardial infarction, deoxycorticosterone acetate salt-induced hypertension, chronic N-nitro-L-arginine methyl ester treatment, and streptozotocin-induced diabetes), a positive correlation between force or plateau tetanic tension and myosin ATPase activity was observed. CONCLUSION: Our results suggest that the myocardium adapts to force generation by increasing or reducing the tension cost to maintain myocardial contractility with a better mechanical advantage.